Métricas m-quasi-Einstein generalizadas em variedades compactas - Fernandes, Francisco Yuri Alves (2012)
The main objective of this paper is to present a generalization of generalized quasi-Einstein metrics to any smooth vector fields. Moreover, we will present some integral formulae for quasi-Einstein metrics defined in a compact manifolds.